1996
DOI: 10.1029/96jb02291
|View full text |Cite
|
Sign up to set email alerts
|

Short slip duration in dynamic rupture in the presence of heterogeneous fault properties

Abstract: Recent studies of strong motion data consistently show that the risetime (duration of slip at particular locations on the fault) is significantly shorter than the overall rupture duration. The physical explanation for this observation and its implications have become central issues in earthquake source studies. Two classes of mechanisms have been proposed to explain short risetimes. One explanation is that velocity-weakening frictional behavior on the fault surface causes the fault to self-heal. This possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
116
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(129 citation statements)
references
References 47 publications
(27 reference statements)
11
116
0
1
Order By: Relevance
“…Factors favoring crack-like behavior in the simulations are relatively smooth initial stresses and weak healing (re-strengthening of the fault) following termination of slip, while slip-pulse behavior arises with heterogeneous initial stresses and strong fault healing following rupture termination. This behavior is consistent with fully dynamical rupture simulations (BEROZA and MIKUMO, 1996;ZHENG and RICE, 1998). In our simulations, healing is set by the rate-state frictional properties and by a dynamic stress overshoot parameter that determines the shear stress at the termination of slip relative to the sliding friction.…”
Section: Model Characteristicssupporting
confidence: 76%
“…Factors favoring crack-like behavior in the simulations are relatively smooth initial stresses and weak healing (re-strengthening of the fault) following termination of slip, while slip-pulse behavior arises with heterogeneous initial stresses and strong fault healing following rupture termination. This behavior is consistent with fully dynamical rupture simulations (BEROZA and MIKUMO, 1996;ZHENG and RICE, 1998). In our simulations, healing is set by the rate-state frictional properties and by a dynamic stress overshoot parameter that determines the shear stress at the termination of slip relative to the sliding friction.…”
Section: Model Characteristicssupporting
confidence: 76%
“…For example, the stress may increase in the beginning of the slip motion (curve (1) in Figure 4a) because of loading caused by advancing rupture, or of a specific friction law such as the state-rate dependent friction law [Dieterich, 1979a[Dieterich, , 1979b. In fact, seismological inversion studies have shown this increase [Quin, 1990;Miyatake, 1992;Mikumo and Miyatake, 1993;Beroza and Mikumo, 1996;Ide, 1997;Bouchon, 1997]. However, this increase is of short duration and the amount of slip during this stage is small so that little energy is radiated.…”
Section: Earthquake Energy Budgetmentioning
confidence: 99%
“…Two classical models have been proposed to explain the short rise time: the self-healing pulselike rupture behavior (e.g., Heaton, 1990;Beeler and Tullis, 1996) and rupture propagation along a heterogeneous fault (e.g., Boatwright, 1988;Beroza and Mikumo, 1996;Day et al, 1998). The first model assumes that the fault could heal itself shortly after the passage of the rupture front, which allows for the rise time to remain short.…”
Section: Rupture Duration Versus Rise Timementioning
confidence: 99%